Strengthening BUMDes Nawangwulan Financial Governance through Accounting Training, Mentoring, and Google Sheets-Based Digital Recording: Penguatan Tata Kelola Keuangan BUMDes Nawangwulan melalui Pelatihan Akuntansi, Pendampingan, dan Pencatatan Digital Berbasis Google Sheets - Andriyan Eka Sapta; Sam’ani; Ida Nurhayati; Tutik Dwi Karyanti; Rudi Handoyono; Lilis Mardiana Anugrahwati; Musyafa Alfarizi; Retno Winarti Handayani; Indra Sukma Subagio (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Village-Owned Enterprises (BUMDes) play a strategic role in improving rural community welfare through the management of local economic potential. However, many BUMDes, including BUMDes Nawangwulan in Kendal Regency, still face challenges in financial governance, such as manual and unsystematic recording, limited use of standardized bookkeeping formats, and low adoption of digital recording tools. This community service activity aimed to strengthen the financial governance of BUMDes Nawangwulan through accounting training, mentoring, and the introduction of a Google Worksheet-based financial recording template. The activity applied a Participatory Rural Appraisal (PRA) approach consisting of four stages: socialization, technical workshop, coaching clinic, and monitoring and evaluation. The program involved 12 BUMDes managers from three business units: Pom Mini Desa, Pasar Desa, and Jembatan Penghubung Antar Kecamatan. The results indicate that the activity provided initial support for improving participants’ understanding of transaction recording, separation of personal and business finances, and the use of simple bookkeeping templates. The program also introduced a digital recording template that can be accessed through smartphones as a practical alternative to manual bookkeeping. The evaluation was conducted qualitatively through observation during one-on-one mentoring; therefore, the findings should be understood as an initial indication of improved awareness and administrative readiness rather than a quantitatively measured increase in competence. This activity contributes to strengthening basic financial administration and supporting more transparent and accountable BUMDes governance.